2019
DOI: 10.5539/jas.v11n14p205
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Estimating Optimum Plot Size for ‘Gigante’ Cactus Pear

Abstract: The optimum plot size for ‘Gigante’ cactus pear can be estimated by several methods; thus, ultimately aiming for efficiency, simple use and high precision, the objective of this study was to compare methods for estimating plot sizes: modified maximum curvature method, Hatheway’s convenient plot size method, linear and quadratic response plateau models, and comparison of variances method for evaluating phenotypic characteristics in experiments with ‘Gigante’ cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
0
12
0
10
Order By: Relevance
“…Applying the methodologies of Smith (1938) and Hatheway (1961) in a set of uniformity trials conducted in different sowing periods and with different cultivars makes it possible to generate useful information to be used as a reference in the planning of experiments with buckwheat crop, aiming at higher experimental precision. These methodologies have been used in beans (MAYOR -DURÁN; BLAIR; MUÑOZ, 2012), sunflower (SOUSA et al, 2015;SOUSA;SILVA;ASSIS, 2016), banana (DONATO et al, 2018, cactus pear (GUIMARÃES et al, 2019;GUIMARÃES et al, 2020) and in species with potential for soil cover, such as: velvet bean (CARGNELUTTI FILHO et al, 2014a); forage turnip (CARGNELUTTI FILHO et al, 2014b); and flax (CARGNELUTTI FILHO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Applying the methodologies of Smith (1938) and Hatheway (1961) in a set of uniformity trials conducted in different sowing periods and with different cultivars makes it possible to generate useful information to be used as a reference in the planning of experiments with buckwheat crop, aiming at higher experimental precision. These methodologies have been used in beans (MAYOR -DURÁN; BLAIR; MUÑOZ, 2012), sunflower (SOUSA et al, 2015;SOUSA;SILVA;ASSIS, 2016), banana (DONATO et al, 2018, cactus pear (GUIMARÃES et al, 2019;GUIMARÃES et al, 2020) and in species with potential for soil cover, such as: velvet bean (CARGNELUTTI FILHO et al, 2014a); forage turnip (CARGNELUTTI FILHO et al, 2014b); and flax (CARGNELUTTI FILHO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining significant results consistent with the proposal of the study at a minimum operational cost depends mainly on increasing experimental precision (DONATO et al, 2018). Thus, there are several promising methods for determining the optimum plot size in basic units, such as Modified Maximum Curvature Method - (LESSMAN and ATKINS, 1963), as verified by Guimarães et al (2019aGuimarães et al ( , 2019b; Comparison of Variances Method (VALLEJO and MENDONZA, 1992), studied by Guimarães et al (2019bGuimarães et al ( , 2019c; Linear Response Plateau Model and Quadratic Response Plateau Model (PARANAÍBA et al, 2009), presented by Guimarães et al (2019b) and Hatheway's Convenient Plot Size (HATHEWAY, 1961), corroborated by Guimarães et al (2020).…”
Section: Introductionmentioning
confidence: 60%
“…Size and shape of experimental plots have been discussed by several papers. Sousa et al (2016, Guimarães et al (2019a, 2019b and Silva et al (2019) reported a reduction in CV with increasing plot size. However, after determining the optimum plot size, no significant increase in precision has been reported with increasing plot size (CARGNELLUTI FILHO et al, 2018).…”
Section: Relation Between Relative Information and Coefficient Of Variationmentioning
confidence: 97%
“…Existem vários métodos que são utilizados para a determinação do tamanho ótimo de parcelas experimentais, dentre eles, o do modelo linear de resposta a platô, o da máxima curvatura modificado e o da comparação das variâncias. O primeiro método foi utilizado por Guimarães et al, (2019a), que determinaram o tamanho de parcelas para características de palma forrageira; Guarçoni et al (2017) determinaram tamanho de parcela para características de repolho e Paranaiba et al (2009) utilizaram em um trabalho de proposição de métodos de estimação do tamanho ótimo de parcelas experimentais.…”
Section: Referencial Teóricounclassified
“…Os mesmos autores acrescentaram que o método estima as variâncias de diferentes tamanhos de parcelas e as compara usando o teste de Bartlett. Guimarães et al, (2019a) e Viana et al (2002) também utilizaram este método para estimar tamanho de parcela em experimentos de palma forrageira e de mandioca. Estes métodos utilizam ensaios em branco ou de uniformidade, onde somente uma variedade é plantada, recebendo as mesmas práticas de cultivo.…”
Section: Referencial Teóricounclassified